2006
DOI: 10.1097/01.acm.0000246751.27480.55
|View full text |Cite
|
Sign up to set email alerts
|

Duty Hours Reforms in the United States, France, and Canada: Is It Time to Refocus Our Attention on Education?

Abstract: Resident duty hours restrictions have now been instituted in many countries worldwide. Such policies have resulted in a broad-based discussion in the medical literature concerning their effects on patient care, resident education, and resident well-being. To better understand the impetuses behind these changes, the authors examine not only the duty hours mandates currently in effect in the United States, Canada, and France, but also the events influencing their independent development in these three countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
0
42
0
1
Order By: Relevance
“…21 Internal medicine residents reported less exposure to formal conferences after the 2003 restrictions on duty hours. 22 Because of its efficiency at delivering content in the …”
Section: Discussionmentioning
confidence: 97%
“…21 Internal medicine residents reported less exposure to formal conferences after the 2003 restrictions on duty hours. 22 Because of its efficiency at delivering content in the …”
Section: Discussionmentioning
confidence: 97%
“…In Ontario, for example, the maximum on-call duration for an anesthesia resident is 25 h (24 plus 1 h for handover). 42 The average weekly work hours of Canadian anesthesia residents are fewer than the upper limits stated in the United States guidelines but more than the European Union directive. Currently, 96% of residents in our study reported work weeks that exceed the current EWTD limit, and 10% of residents reported work weeks that exceed the United States guidelines.…”
Section: Work Hour Reformsmentioning
confidence: 99%
“…20,21 In France, resident duty hours were restricted to 52.5 hours per week. 22 The National Ministry of Health of Argentina establishes that residents should work, at least, 48 hours per week and complete not more than eight on-duty shifts per month. 4 There is evidence that an excessive work load and an inequitable distribution of duties lead to burnout 19,23,24 and cause high rates of depersonalization and emotional exhaustion among residents.…”
Section: Predictors Of Vacancy Fillingmentioning
confidence: 99%